PERNIKAHAN USIA DINI PADA PEREMPUAN DI DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR - Yuliana Citra; Swiss Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study was conducted at Desa Pulau Jambu Kecamatan Kuok. Tujuan dari penelitian ini adalah untuk mengetahui akibat dari pernikahan usia dini pada perempuan at Desa Pulau Jambu Kecamatan Kuok. The focus of this research is to analyze the factors behind the early marriage of women at Desa Pulau Jambu Kecamatan Kuok. Limitations possessed by the author in terms of time and cost so the authors decided to take as many as 3 informants only through sampling technique that is purposive sampling technique. Data instruments are observation, interview and documentation.From the research conducted, the authors found that there are several factors behind the early marriage of women at Desa Pulau Jambu Kecamatan Kuok, Namely: Factors of Intercourse, the progress of the times has brought the subject of research far from warned-warned both parents and extended family. The subject of research is more afraid if he is ostracized by his friends because it is considered old-fashioned and does not follow the trends of today's teenagers. Economic Factors, If only for school, the research subject parents can afford it. But not for the lifestyle interests of research subjects who follow all the lifestyle of his friends. Environmental Factor, Subject of research. Revealed that to get married young in the village of Jambu Island is common. There are many early childhood children who decide to get married after graduating from junior high school. The impact of early marriage to research subjects in the village of Jambu Island is as follows: Divorce, Early marriage in the village of Jambu Island has a negative impact for the perpetrators. Not a few junior high school girls decide to get married because of various factors and decided to divorce due to certain factors as well. Young Maternal Risk, the subject of research, when the birth is not only faced with a declining body health condition, but also faced with unhealthy infant condition and even died during childbirth.Keywords: Driving Factors, the Impact of Early, Marriage